Research hotspots and global trends in respiratory syncytial virus over past five years - Tao, Xiaoli; Ma, Zhuping; Yuan, Hongxia; Zhao, Wei; Liu, Jingyu; Tian, Jing (Frontiers in Microbiology, 2025)
Respiratory syncytial virus (RSV) is the main cause of acute lower respiratory tract infections in children under 2 years old. This bibliometric analysis is used to determine the characteristics, hotspots, and frontiers of RSV global scientific output over the past 5 years. In this study, the Science Citation Index Expanded (SCI-Expanded) version from the Web of Science Core Collection (WoSCC) for publications and record information published from 2020 to 2024 was retrieved. Bibliometric software package was used to analyze the bibliometric indicators, and the research trends and hotspots of RSV were visualized by VOSviewer and Citespace. We assessed paper influence with the Global Citation Score (GCS). A total of 7,238 articles and comments were searched. The USA is the most productive country in the field of RSV research and also the country with the closest cooperation with other countries and institutions. The most influential journal in this field is “VIRUSES BASEL” with 246 publications. The co-citation analysis of references showed that the RSV-related topics with the highest focus are “covid-19 pandemic,” “respiratory syncytial virus prefusion,” “American academy,” and “protein vaccine.” From 2020 to 2024, keyword cluster and keyword burst analyses showed that “Respiratory Syncytial Virus,” “Infection,” and “Children.” “Viral co-infection,” “anti-virus,” and “vaccines” are currently research hotspots. The research area in this field is mainly distributed among “Immunology,” “Pediatrics,” “Pharmacology Pharmacy,” and “Biochemistry Molecular Biology.” Our study highlights the trends and hotspots in the field of RSV research over the past 5 years. Identifying the most critical indicators in the field of RSV research would be able to help researchers in this field better understand RSV and make decisions.